The royal artisan - Afshar, Tessa (Afshar, Tessa. Queen Esther's court., 2025)
"In ancient Persia, Sazana creates exquisite pottery as Queen Esther's artisan but keeps her Jewish identity hidden from her tyrannical master, Haman, and his ten vengeful sons. When tragedy strikes, Sazana must join forces with Jadon, the man who broke her heart, to locate an ancient artifact and thwart the impending threat to their people"--